ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI PERBANDINGAN - Benisius Kardo; Maria Gracia Manoe Gawa (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to analyze students' errors in solving mathematics problems on the topic of ratios in grade VII at SMP NCIPS Kupang. The research method used is qualitative descriptive, with three students selected based on their ability levels: high, medium, and low. The research instruments included a diagnostic test with two essay questions and interviews to explore the causes of students' errors. Data analysis was conducted using the Newman Error Analysis stages, which include reading, understanding, transformation, process skills, and writing the final answer. The results show that high-ability students only made errors in the final answer writing stage, while medium-ability students often made errors in understanding the question, transformation, and calculation stages. Low-ability students encountered difficulties in almost all stages, particularly in understanding the question and transforming the problem into the correct mathematical form. The most dominant errors were found in understanding the question and transforming the problem. Factors causing these errors include a lack of understanding of the concept of ratios, misconceptions between direct and inverse ratios, and rushing through the problem-solving process. These findings are expected to provide valuable insights for teachers in designing more effective learning strategies to improve students' problem-solving skills. ABSTRAK Penelitian ini bertujuan untuk menganalisis kesalahan siswa dalam menyelesaikan soal matematika materi perbandingan pada kelas VII SMP NCIPS Kupang. Metode yang digunakan adalah deskriptif kualitatif dengan subjek tiga siswa yang dipilih berdasarkan tingkat kemampuan: tinggi, sedang, dan rendah. Instrumen penelitian berupa tes diagnostik yang berisi dua soal uraian dan wawancara untuk menggali penyebab kesalahan. Analisis data dilakukan menggunakan tahapan Analisis Kesalahan Newman, yang meliputi tahap membaca, memahami, transformasi, keterampilan proses, dan penulisan jawaban akhir. Hasil penelitian menunjukkan bahwa siswa berkemampuan tinggi hanya mengalami kesalahan pada tahap penulisan jawaban akhir, sementara siswa dengan kemampuan sedang sering melakukan kesalahan pada tahap pemahaman soal, transformasi, dan perhitungan. Siswa berkemampuan rendah mengalami kesulitan di hampir seluruh tahap, terutama dalam memahami soal dan mengubah informasi ke bentuk matematika yang tepat. Kesalahan yang paling dominan ditemukan pada pemahaman soal dan transformasi masalah. Faktor penyebab kesalahan antara lain kurangnya pemahaman konsep perbandingan, miskonsepsi antara perbandingan senilai dan berbalik nilai, serta terburu-buru dalam menyelesaikan soal. Temuan ini diharapkan dapat memberikan wawasan bagi guru dalam merancang strategi pembelajaran yang lebih efektif untuk meningkatkan kemampuan pemecahan masalah siswa